REVITALIZING COMPETITIVENESS: ENHANCING THE MECHANISM FOR MANAGING INDUSTRIAL ENTERPRISE COMPETITIVENESS - Ergashev Xayotbek Abdiqaxarovich (Miasto Przyszłości, 2023)
This article explores evidence-based strategies for improving the management of competitiveness in industrial enterprises. It begins by providing a background on the significance of competitiveness and an overview of the current challenges in managing it. The importance of competitiveness in the industrial sector, factors influencing competitiveness, and its relationship with sustainable growth are discussed. The article concludes by emphasizing the importance of managing competitiveness in industrial enterprises and provides a call to action for organizations to prioritize competitiveness in their management approach. It highlights the potential benefits and long-term impact of an improved competitiveness management mechanism.